LAFAZ DITINJAU DARI SEGI CAKUPANNYA (‘ÂM - KHÂS - MUTHLAQ - MUQAYYAD) - Muhammad Amin Sahib (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2016)
Lafaz is an expression to understand a thing. The meaning of lafaz was strongly influenced by anything that followed it.Lafadz could have significant meaning:âm (general), khâs (specific), muthlaq (definite) and muqayyad (bound). This article explains how lafadz has a general, specific, definite, and bound meaning to explain the rules / regulations that may affect it. It exposed them by mentioning some opinions and compared them with examples from the Koran and Hadith to find a more clear understanding of the arguments of Syara’.